Comprehensive Physiology 2015
DOI: 10.1002/cphy.c140082
|View full text |Cite
|
Sign up to set email alerts
|

Aging Effects on Cardiac Progenitor Cell Physiology

Abstract: Cardiac aging has been confounded by the concept that the heart is a postmitotic organ characterized by a predetermined number of myocytes, which is established at birth and largely preserved throughout life until death of the organ and organism. Based on this premise, the age of cardiac cells should coincide with that of the organism; at any given time, the heart would be composed of a homogeneous population of myocytes of identical age. The discovery that stem cells reside in the heart and generate cardiac c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 359 publications
(527 reference statements)
1
18
0
Order By: Relevance
“…In vitro sex-related biological responses | 18289 of human CPC have been described for TNF-α signaling (Straface et al, 2017). Age-related differences in CPC have also been reported (Rota, Goichberg, Anversa, & Leri, 2015). Our current study is limited with a focus on young male mice.…”
Section: Discussionmentioning
confidence: 94%
“…In vitro sex-related biological responses | 18289 of human CPC have been described for TNF-α signaling (Straface et al, 2017). Age-related differences in CPC have also been reported (Rota, Goichberg, Anversa, & Leri, 2015). Our current study is limited with a focus on young male mice.…”
Section: Discussionmentioning
confidence: 94%
“…; Rota et al . ). Skeletal muscle stem cells in aged mice also have elevated expression of p16; this contributes to a switch from quiescent to senescent and their lack of activation upon injury (Sousa‐Victor et al .…”
Section: Discussionmentioning
confidence: 97%
“…This is in line with a previous study in which it was reported that CPCs isolated from 13-month FVBN mice presented flattened morphology and greater SA-β-Gal expression than a younger FVBN cohort . It has also been shown that p16 accumulates in various stem/progenitor cells including the brain, bone marrow, pancreas and heart in aged rodents (Krishnamurthy et al 2004;Torella et al 2004; Molofsky et al 2006;Rota et al 2015). Skeletal muscle stem cells in aged mice also have elevated expression of p16; this contributes to a switch from quiescent to senescent and their lack of activation upon injury (Sousa-Victor et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sca-1 + cells in cardiac tissue may be the most common CSC/CPCs and be relatively easy to isolate [4], Sca-1 + CD31 − cells show cardiomyogenic differentiation and cell transplantation for myocardial repair [5, 6]. Changes in the properties of CSC/CPCs with age involving increased symmetric division, decreased cell proliferation and differentiation, loss of self-renewing capacity, partial depletion of the primitive pool, decreased expression of stem cell markers, impaired the migration ability, and changed the cell cycle into an irreversible quiescent state [79]. However, some other reports suggested that the impact of age on the quantity and quality of human cardiac stem cells is quite limited [10].…”
Section: Introductionmentioning
confidence: 99%